2023
DOI: 10.3390/tropicalmed8040210
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Plasmodium vivax Field Isolates from the Thai–Myanmar Border during the Period of 2006–2016

Abstract: High levels of genetic variants of Plasmodium vivax have previously been reported in Thailand. Circumsporozoite surface protein (CSP), merozoite surface protein (MSP), and microsatellite markers were used to determine the genetic polymorphisms of P. vivax. This study aimed to investigate the molecular epidemiology of P. vivax populations at the Thai–Myanmar border by genotyping the PvCSP, PvMSP-3α, and PvMSP-3β genes. Four hundred and forty P. vivax clinical isolates were collected from the Mae Sot and Sai Yok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, the genetic diversity of P. vivax populations is not fully captured by this basic genotyping 19 . One longitudinal study identified 14 different Pv CSP alleles in patients at the Thai-Mayanmar border 20 while another identified 67 unique P. vivax merozoite surface protein 1 ( Pv MSP-1) haplotypes 21 . A large proportion of recurring P. vivax cases are heterologous infections and contain different parasite genotypes than acute infection 22 , with a particularly high level of genetic diversity in parasites circulating in and around Thailand 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the genetic diversity of P. vivax populations is not fully captured by this basic genotyping 19 . One longitudinal study identified 14 different Pv CSP alleles in patients at the Thai-Mayanmar border 20 while another identified 67 unique P. vivax merozoite surface protein 1 ( Pv MSP-1) haplotypes 21 . A large proportion of recurring P. vivax cases are heterologous infections and contain different parasite genotypes than acute infection 22 , with a particularly high level of genetic diversity in parasites circulating in and around Thailand 22,23 .…”
Section: Introductionmentioning
confidence: 99%